Negative impedance elements and their applications in antenna miniaturization - Zheng, Yujia. (2011)
Electrically small antennas present high-Q impedance characterized by large reactance and small radiation resistance. For such antennas, the effectiveness of passive matching is severely limited by gain-bandwidth theory, which predicts narrow bandwidths and/or poor gain. It is possible in theory to transform the antenna into an active component that is no longer limited by the gain-bandwidth-size. The technique of non-foster impedance matching employs active networks of negative impedance converters (NICs) such as negative inductors and capacitors to bypass the restrictions of gain-bandwidth theory. This report mainly focuses on how to realize the negative impedance converters and their applications in antenna miniaturization design.